Influence Characteristics Auditor Partner and Kap Size on Audit Quality - Kadlina; Agus Munandar (AFRE (Accounting and Financial Review), 2025)
This study aims to examine the effect of auditor partner characteristics and Public Accounting Firm (KAP) size on audit quality. The auditor partners’ characteristics include gender, level of education, work experience, level of busyness in the same industry, and domestic or international educational background. KAP size is determined by inclusion in Big Four public accounting firms, while audit fees or professional fees measure audit quality. Using panel data regression, the findings reveal that auditor partner experience significantly enhances audit quality, demonstrating the importance of technical expertise and professional judgment. Additionally, KAP size consistently influences audit quality, emphasizing the role of firm resources, specialize skills, and reputation. JEL Classification: M40, M41, M42 DOI: https://doi.org/10.26905/afr.v8i2.15232